PRONUNCIATION ERRORS AMONG MALAYSIAN UNDERGRADUATES IN ENGLISH FOR ORAL COMMUNICATION COURSE - Chelster Sherralyn Jeoffrey Pudin; Nik Zaitun Nik Mohamed; Wardatul Akmam Din; Eugenia Ida Edward, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In a country where there is a diverse range of races and cultures, the influence of the first language comes almost naturally when using English as a second language. This influence has created a negative transfer which has affected learners’ communicative competence as well as performance. This study intends to investigate the pronunciation errors among undergraduates in a Malaysian university and explain the mispronunciations by comparing the phonetic system of English and Malay It is hoped that the results of this study will eventually provide some insights to producing effective strategies for teaching pronunciation that can help ESL learners to improve their oral proficiency skills and thus meeting their personal and professional needs.